Creatine monohydrate supplementation reduces muscle damage and player load index in young semi-professional Colombian football players - Luis H. Palma-Pulido; Julián A. Guío-Bácares; Yamir M. Palacios-Ruales; Diego A. Bonilla (Journal of the International Society of Sports Nutrition, 2025)
Background Creatine monohydrate supplementation has benefits on strength performance and body composition; however, its potential in reducing exercise-induced muscle damage and moderating training load in soccer players remains understudied. The study aimed to evaluate muscle damage and training load following a 10-week supplementation period with CrM with and without whey protein in semi-professional Colombian football players.Methods Twenty-eight male semi-professional soccer players (competing in Colombian U17, U20, and 1C leagues) were randomized into four groups: whey protein (25 g/day; n=5), CrM (5 g/day; n=7), CrM + protein (n=10), or placebo (n=6). The 10-week intervention was conducted alongside regular training. Total serum creatine kinase (CK) levels were assessed biweekly, 48–72 h post-training to capture exercise-induced muscle damage. Training load was monitored via Catapult GPS tracking. Player load was the sum of the accelerations across all axes of the internal tri-axial accelerometer during movement.Results No significant differences in CK levels were observed between time points for placebo, protein, or CrM groups. However, the CrM + whey protein group showed a statistically significant reduction in CK levels (P=0.035), suggesting a synergistic effect on muscle recovery. Notably, high-intensity actions under one minute (RHIE) and player load showed significant improvements in the CrM + protein group. Both protein and CrM groups showed significant body fat reduction (p<0.001), while only the group CrM + whey protein experienced a significant increase in the estimates of muscle mass (p=0.031).Conclusions Consuming CrM plus whey protein reduces muscle damage and training load while producing favorable changes in body composition in semi-professional soccer players. These findings should be incorporated into nutritional strategies for athletes facing demanding training and competition schedules.